The use of geographic information systems and remote sensing to detect soil dryness in Yathrib district in terms of soil moisture index (NDMI) and vegetation cover index (NDVI) - Osama, Qods (Al-Adab Journal, 2023)
The study dealt with the process of detecting soil dryness in Yathrib district using geographic information systems and remote sensing methods for the period (1990-2020) by following up the soil moisture index (NDMI) and the vegetation cover index (NDVI) for the year 1990 and determining the areas of each indicator, and then following up the change The holder of the two indicators for the same region for the year 2020. And the production of digital maps for each indicator and according to the selected years.The study concluded that lands with a low moisture index (dry soils) occupied an area of ​​(143.2 km2), equivalent to (54.5%) of the area of ​​the district in 1990, while wet lands occupied an area estimated at (119.6 km2), equivalent to (45.5%). for the same year.While in the year 2020 the area of ​​dry lands amounted to (243.3 km2), equivalent to (92.6%) of the area of ​​the study area.As for the vegetation cover index (NDVI), the study found that barren lands with weak vegetation covered an area of ​​(103.3 km2), which is equivalent to (39.3%) of the total area of ​​the region in 1990, but in 2020, the area of ​​barren and covered lands reached Little (158.3 km2), equivalent to (60.2%) of the region's area.The study concluded that there is a positive relationship between the soil moisture index (NDMI) and the vegetation cover index (NDVI).